Modern priorities of energy policy of Kazakhstan in the Сaspiаn region - L. A. Parkhomchik (Проблемы постсоветского пространства, 2017)
Deepening negative tendencies in the economy of Kazakhstan causes the necessity to develop comprehensive measures for both maintaining and intensifying the development of the oil and gas extracting industry, which is still a backbone industry of the national economy. For that reason, the most important thing for further economic growth is updating the strategy of the Caspian regions of Kazakhstan as the most oil and gas reached areas of the state. Therefore, the article examines the key issues of the Kazakhstani energy sector development in the contemporary geo-economic realities.